Effect of Different Stocking Density on Growth and Survival Rate of Blue Swimming Crab(Portunus pelagicus)in Recirculation System - Yesi Yonna Haliza; Niken Ayu Pamukas; Mulyadi Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTBlue swimming crab is fisheries commodity having high economic value. The aim of  study is  to knowthe best stocking density on growth and survival rate of blue swimming crab (Portunus pelagicus) in recirculation system. This research was conducted in July-August 2019. Located in Center for Brackish A quaculture Fisheries (BBPBAP) Jepara. The methods used was the exprerimental method, namely a completely randomized design (CRD) ofone factor with four levels of treatment and three replications required 12 experimental units with treatments P1 = 8 ind/32 liters, P2 = 10 ind/32 liters, P3 = 12 ind/32 liters and P4 = 14 ind/32 liters.The best growthrates was found in P1with stocking density of 8 ind/32 L with absolute weight growth 1.60 g,  the specific growth 8.81 g and survival rate 58.33%. Water quality during research were 25,1 -28, 90°C, pH 7.51-7.72, 4.21-6.04 mg/L dissolved oxygen and ammoniac 0.001-0.072 mg/L.Keywords: Blue swimming Crab, Stocking Density, Growth